Widespread expression of glycine receptor subunit mRNAs in the adult and developing rat brain. - Malosio, M L (1991)
The inhibitory glycine receptor (GlyR) is a ligand-gated ion channel which mediates post-synaptic inhibition in spinal cord and other regions of the vertebrate central nervous system. Previous biochemical and molecular cloning studies have indicated heterogeneity of GlyRs during development. Here, the distribution of GlyR subunit transcripts in rat brain and spinal cord was investigated by in situ hybridization using sequence-specific oligonucleotide probes. In adult animals, GlyR alpha 1 subunit mRNA was abundant in spinal cord, but was also seen in a few brain areas, e.g. superior and inferior colliculi, whereas alpha 2 transcripts were found in several brain regions including layer VI of the cerebral cortex and hippocampus. GlyR alpha 3 subunit mRNA was expressed at low levels in cerebellum, olfactory bulb and hippocampus, while high amounts of beta subunit transcripts were widely distributed throughout spinal cord and brain. During development, alpha 2 mRNA accumulated already prenatally and decreased after birth, whereas alpha 1 and alpha 3 subunit transcripts appeared only in postnatal brain structures. Hybridization signals of beta subunit mRNA were seen already at early embryonic stages and continuously increased to high levels in adult rats. These data reveal unexpected differences in the regional and developmental expression of GlyR subunit mRNAs and point to novel functions of GlyR proteins in the mammalian central nervous system.